Urokinase Plasminogen Activator Receptor (uPAR) Targeted Therapy with Switchable Chimeric Antigen Receptor T-Cell (sCAR T-Cell) Potential as Pancreatic Cancer Immunotherapy Agent - Umar, Tungki Pratama; Ramadhan, Muhammad Syahrul; Mahfuza, Nindya (International Journal of Human and Health Sciences (IJHHS), 2020)
Pancreatic cancer is the cancer with highest mortality-incidence rate compared with other types of cancer. Most cases can only be treated palliatively. Targeted therapy comes as an alternative to its treatment especially with Switchable CAR T-cells (sCAR T-cells). In pancreatic cancer, urokinase plasminogen activator receptor (uPAR) is a specific target that is excessively expressed in tumor cell microenvironment. Targeted therapy using sCAR T-cells has been proved safe and effective in other types of malignancy such as B cell lymphoma, so it has potency as immunotherapy agent in pancreatic cancer patient. International Journal of Human and Health Sciences Vol. 05 No. 02 April’21 Page: 171-176